A Narrative Study of Teachers' Challenges in Teaching Indonesian Language in Remote Areas: Challenges, Institutional Support, Teaching Strategies - Putri Hafidzah; Sri Maryani; Baiq Yuliatin Ihsani (Indonesian Language Education and Literature, 2025)
This study aims to explore the challenges teachers face in teaching Indonesian in remote areas, as well as identify the forms of institutional support and learning strategies implemented. Using a qualitative method with a narrative study approach, data were collected through observation and in-depth interviews with teachers and principals in public and private junior secondary schools in remote areas. Data analysis refers to the Miles and Huberman interactive model. The results showed that teachers face challenges in the form of limited infrastructure, books, learning support tools, minimal institutional support for professional development, and low student interest in learning. Support from the government and educational institutions is still limited. In dealing with these conditions, teachers tend to use lecture, question-and-answer, and discussion strategies that are adjusted to the limitations in the field. This research is expected to be an input for policymakers in improving shared learning in remote areas.Studi Naratif tentang Tantangan Guru dalam Mengajar Bahasa Indonesia di Daerah Terpencil: Tantangan, Dukungan Kelembagaan, Strategi PengajaranPenelitian ini bertujuan untuk mengeksplorasi tantangan yang dihadapi guru dalam mengajar Bahasa Indonesia di daerah terpencil, serta mengidentifikasi bentuk dukungan institusional dan strategi pembelajaran yang diterapkan. Menggunakan metode kualitatif dengan pendekatan studi naratif, data dikumpulkan melalui observasi dan wawancara mendalam dengan guru dan kepala sekolah di SMP negeri dan swasta di wilayah terpencil. Analisis data mengacu pada model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa guru menghadapi tantangan berupa keterbatasan sarana prasarana, buku, alat penunjang pembelajaran, minimalnya dukungan institusi untuk pengembangan profesional, serta rendahnya minat belajar siswa. Dukungan dari pemerintah dan lembaga pendidikan dinilai masih terbatas. Dalam menghadapi kondisi tersebut, guru cenderung menggunakan strategi ceramah, tanya jawab, dan diskusi yang disesuaikan dengan keterbatasan di lapangan. Penelitian ini diharapkan dapat menjadi masukan bagi pengambil kebijakan dalam meningkatkan pembelajaran bersama di daerah terpencil.